Dedifferentiated Leiomyosarcoma of the Auricle with Heterologous Osteosarcoma Component: Case Report and Literature Review - Andrea Dekanić; Nives Jonjić; Anita Savić Vuković (Case Reports in Otolaryngology)
Leiomyosarcomas are rare malignant tumors of smooth muscles. Head and neck involvement by this disease is very rare, and cutaneous leiomoysarcomas of the ear are even rarer. This is way clinically they are usually mistaken for either squamous or basal cell carcinomas, as was the case in an 85-year-old male patient presented in this report. However, the final diagnosis was even more interesting considering that it was a dedifferentiated leiomyosarcoma of the auricle with a heterologous component of osteosarcoma. The auricular cutaneous malignancies have a much higher rate of recurrence than the corresponding malignancy in other regions of the head and neck, even when resected with negative surgical margins, and dedifferentiated leiomyosarcoma is clinically even more aggressive. Thus, the treatment of choice is a total auriculectomy and great attention should be paid to appropriate margins.